2020
DOI: 10.1371/journal.pone.0234382
|View full text |Cite
|
Sign up to set email alerts
|

A brief exposure to rightward prismatic adaptation changes resting-state network characteristics of the ventral attentional system

Abstract: A brief session of rightward prismatic adaptation (R-PA) has been shown to alleviate neglect symptoms in patients with right hemispheric damage, very likely by switching hemispheric dominance of the ventral attentional network (VAN) from the right to the left and by changing task-related activity within the dorsal attentional network (DAN). We have investigated this very rapid change in functional organisation with a network approach by comparing restingstate connectivity before and after a brief exposure i) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 84 publications
(141 reference statements)
0
9
0
Order By: Relevance
“…To that end, we generated similar connectivity matrices from our previously published data, in which resting state fMRI was collected before and after a brief exposure to rightward-shifting PA goggles (see Wilf et al. 2019 ; Gudmundsson et al. 2020 for details).…”
Section: Resultsmentioning
confidence: 99%
“…To that end, we generated similar connectivity matrices from our previously published data, in which resting state fMRI was collected before and after a brief exposure to rightward-shifting PA goggles (see Wilf et al. 2019 ; Gudmundsson et al. 2020 for details).…”
Section: Resultsmentioning
confidence: 99%
“…Our finding of an enhanced decoupling between DMN/FPN regions and dorsal and ventral attentional networks after VRPA (see Figure 3b ), more pronounced in the hemisphere contralateral to the shift, is consistent with recent studies that measured standard PA aftereffects in resting state connectivity (Schintu et al ., 2019; Tsujimoto et al ., 2019; Wilf et al ., 2019; Gudmundsson et al ., 2020). We suggest that the bottom-up learning process during adaptation eventually propagates forward in the processing pathway to affect high-level, heteromodal, cortical networks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that the aftereffects of PA manifest also in brain activity as changes in activation of the inferior-parietal lobule (IPL; Crottaz-Herbette et al ., 2014; Crottaz-Herbette et al ., 2017b), a key area at the intersection between the attentional networks and the DMN. In addition to its effect on task-induced activation, PA has been recently found to modulate task-free resting-state connectivity, inducing enhanced decoupling between the attentional networks and the DMN (Wilf et al ., 2019) or a modulation of the right/left fronto-parietal networks (Schintu et al ., 2019; Tsujimoto et al ., 2019; Gudmundsson et al ., 2020; see Panico et al ., 2020 for review).…”
Section: Introductionmentioning
confidence: 99%
“…In a first study, global connectivity analysis revealed significant decreases in functional connectivity of nodes within left IPL and left insula as well as bilaterally within the medial prefrontal cortex, revealing a reduction of the connectivity between the Default Mode Network and the attentional network ( Wilf et al, 2019 ). In a second study, whole brain analysis using the graph theory approach revealed a decrease in connectivity strength and in local efficiency in VAN, but not DAN ( Gudmundsson et al, 2020 ). A third study carried out seed-based correlation analysis within the attentional network before and after a brief exposure to R-PA, without a control group ( Tsujimoto et al, 2019 ).…”
Section: Prism-induced Topographical Mismatch Reshuffles Spatial Repr...mentioning
confidence: 95%